Religiosity as a Predictor of Consumer Ethical Behaviour: Some Evidence From Young Consumers From Malaysia - Ramly , Zulkufly; Chai , Lau Teck; Lung , Choe Kum (Journal of Law and Governance, 2008)
Young consumers group has been a growing population of consumers in Malaysia. The group is increasingly cosmopolitan in its outlook and preferences, and highly exposed to various media and advertising tactics. As Malaysia is rapidly moving towards industrialised and modern economy, the changing socio-economic factors, growing affluence and declining moral and religious standards, especially in urban areas can play an important role in shaping the ethical orientation of young consumers. This research examined the role of religiosity in determining the ethical attitudes of young consumer groups in Malaysia. Undergraduate students represent the new generation of young consumers group. Hence, two hundred and seventy eight undergraduate business and accounting students in public and private universities in Kuala Lumpur, Malaysia were surveyed for this purpose. This research found limited evidence to support the hypothesis that religiosity was a positive determinant of young consumers’ ethical beliefs in Malaysia. Further, the results also revealed that male young consumers were more willing to benefit from illegal activities as well as to passively benefit at the expense of others than did the female students.